Are Product Owners communicators? A multi‐method research approach to provide a more comprehensive picture of Product Owners in practice. Issue 1 (27th August 2020) - Unger‐Windeler, Carolin; Klünder, Jil Ann‐Christin; Reuscher, Timothy; Schneider, Kurt
Abstract: Product Owners have an important role in the agile and hybrid software development process. While this role is supposed to maximize the value of a product, there seem to be several scattered results on how they achieve this, as well as what actually constitutes this role in practice. To consolidate current research results and to further analyze the key attribute of Product Owners, we conducted a multi‐method research approach spanning a systematic mapping study and a consecutive case study in a hybrid development environment. The results of the mapping study states that Product Owners are communicators. We further investigated on this and used the shadowing technique to observe three Product Owners' communication activities. The results support that statement, as the gained data reveal that Product Owners spend 65% of their time in meetings. But rather than just providing the team with the necessary requirements for the product under development, Product Owners need this time to synchronize and align their work, streamline the agile process of large‐scale Scrum, discuss team‐based topics, and to solve upcoming issues addressed by the team. These results contribute to draw a more comprehensive picture of the important but yet complex role of Product Owners in practice.